The Development of Guidelines for Prevention and Control of Tuberculosis for New Pulmonary Tuberculosis Patients and Their Household Contacts in Health Network of Kaset Wisai District, Roi Et Province - วานิชชัง, ยุวดี; บุญศล, จารุวรรณ; ถนัดค้า, อาภรณ์ (Disease Control Journal, 2018)
This study aimed to identify problems and obstacles that prevent health authorities from implementing a more effective TB control in Kaset Wisai district, Roi Et province, Thailand. Baseline data on TB control performance were collected and analyzed. The study populations included TB patients with positive sputum smear (SS+) and their household contacts. A total of 127 participants were enrolled into the study. Prior to the intervention, a set of questionnaires relevant to TB was developed and edited by five TB specialists. The approved questionnaires were administered to test pre-study knowledge and practices of new SS+ TB cases and their household contacts (n = 127). After questionnaire administration, utilizing descriptive statistics, data were collected, analyzed, and presented by percentage, frequency, mean and standard deviation. The results of data analysis indicated that the knowledge of new SS+ PTB cases and their household contacts was remarkably low (63.4%). Nevertheless, after the training their knowledge was found to have significantly improved (87.9%). The significant improvement was also seen among their close contacts (from 45.4% to 85.7%). An in-depth interview was conducted among multidisciplinary health care workers (n = 27) to identify the needs for improvement of knowledge and practices among the patients and their close contacts. The lack of good coordination among health care workers at various levels was also noted and more effective communication was needed. Existing TB infection control measures also needed to be adequately addressed. We recommend that in patient care settings with low success rates, the responsible team should adopt this approach to improve their performance.